2016
DOI: 10.1136/thoraxjnl-2015-208039
|View full text |Cite
|
Sign up to set email alerts
|

Chronic electronic cigarette exposure in mice induces features of COPD in a nicotine-dependent manner

Abstract: BackgroundThe use of electronic (e)-cigarettes is increasing rapidly, but their lung health effects are not established. Clinical studies examining the potential long-term impact of e-cigarette use on lung health will take decades. To address this gap in knowledge, this study investigated the effects of exposure to aerosolised nicotine-free and nicotine-containing e-cigarette fluid on mouse lungs and normal human airway epithelial cells.MethodsMice were exposed to aerosolised phosphate-buffered saline, nicotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
263
6
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(314 citation statements)
references
References 35 publications
(35 reference statements)
23
263
6
3
Order By: Relevance
“…Traditionally, nicotine has been studied as the addictive component in cigarettes, but increasing evidence has indicated that nicotine is also a key factor in the initiation and progression of COPD. Nicotine hinders the hydration of mucus, promotes cell proliferation by causing calcium influx in ASMCs, induces pro-inflammatory dendritic cell responses, and blocks neutrophil apoptosis [31]. Despite the absence of a clear understanding of nicotine-induced health risk, some manufacturers have suggested that using nicotine can help someone who extensively smoke quit their smoking habit, which is widely known to be hazardous to health.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, nicotine has been studied as the addictive component in cigarettes, but increasing evidence has indicated that nicotine is also a key factor in the initiation and progression of COPD. Nicotine hinders the hydration of mucus, promotes cell proliferation by causing calcium influx in ASMCs, induces pro-inflammatory dendritic cell responses, and blocks neutrophil apoptosis [31]. Despite the absence of a clear understanding of nicotine-induced health risk, some manufacturers have suggested that using nicotine can help someone who extensively smoke quit their smoking habit, which is widely known to be hazardous to health.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports of rapid-onset changes in aortic stiffness after exposure to vape,8 of mice exposed to vape with nicotine developing features of chronic obstructive pulmonary disease9 and a 2014 report of increases in fractional exhaled nitric monoxide (FeNo),5 a marker of eosinophilic airway inflammation, following vaping are examples of possibly vanguard research findings that may prove important.…”
Section: Not Just Water Vapourmentioning
confidence: 99%
“…While documented indoor concentrations of exhaled vape constituents are often lower than those arising from cigarettes,9 real world scenarios can involve significant exposure. Scenes from ‘vapecons’ abound on YouTube,11 where large numbers of ENDS users participate in ‘clouding’ contests, show worst case scenarios (eg, http://www.youtube.com/watch?v=4NPe3rAYG_Q&t=0m46s).…”
Section: Real World Exposuresmentioning
confidence: 99%
“…This suggests that targeting autoimmunity in at-risk patients could be a novel strategy to prevent ILD 8. Professor Foronjy (New York, USA) demonstrated that inhaled nicotine e-cigarette solution leads to airway inflammation and airspace enlargement in mice, suggesting that in addition to being the addictive component of cigarettes, nicotine also plays a key role in the initiation and progression of COPD 9. Finally, Dr Melissa McDonnell (Newcastle) discussed different bronchiectasis severity measures in seven European cohorts, and showed that the Bronchiectasis Severity Index was superior at predicting clinically useful outcomes such as hospitalisation, exacerbations, lung function decline and quality of life 10…”
Section: Introductionmentioning
confidence: 99%